Returning to the Essence of Education: The Corrective Path and Bottom-Line Adherence of Study Tour Practical Education - Xiulong Guo; Ran Cao (Education Research on Study Tours and Practice, 2026)
Against the backdrop of the in-depth advancement of the Double Reduction Policy and fostering virtue through education, research-based practical education has become a core carrier connecting classroom learning in schools with social education and realizing the integration of five types of education. Located at the junction of urban and rural areas, county-level junior high schools feature abundant local resources yet limited educational resources. Their research-based practical education is confronted with common problems including fragmented curriculum, formalistic activities and unitary evaluation, while boasting unique merits such as local culture, ecological resources and labor practice scenarios. From the theoretical perspective of integrated five-type education, this paper takes the practical exploration of research-based education at No.3 Middle School of Baiquan County as a case, systematically analyzes the practical dilemmas and resource endowments of research-based education in county-level junior high schools. It constructs a feasible, replicable and promotable development path from five dimensions: objective system, curriculum development, implementation mechanism, evaluation reform and guarantee support, providing theoretical reference and practical experience for county-level junior high schools to deepen quality-oriented education and boost students’ all-round development.